In situ reduction of gold nanoparticles-decorated MXenes-based electrochemical sensing platform for KRAS gene detection - Yu, Xiongtao; Bai, Silan; Wang, Lishi (Frontiers in Bioengineering and Biotechnology, 2023)
In this work, gold nanoparticles@Ti3C2 MXenes nanocomposites with excellent properties were combined with toehold-mediated DNA strand displacement reaction to construct an electrochemical circulating tumor DNA biosensor. The gold nanoparticles were synthesized in situ on the surface of Ti3C2 MXenes as a reducing and stabilizing agent. The good electrical conductivity of the gold nanoparticles@Ti3C2 MXenes composite and the nucleic acid amplification strategy of enzyme-free toehold-mediated DNA strand displacement reaction can be used to efficiently and specifically detect the non-small cell cancer biomarker circulating tumor DNA KRAS gene. The biosensor has a linear detection range of 10 fM -10 nM and a detection limit of 0.38 fM, and also efficiently distinguishes single base mismatched DNA sequences. The biosensor has been successfully used for the sensitive detection of KRAS gene G12D, which has excellent potential for clinical analysis and provides a new idea for the preparation of novel MXenes-based two-dimensional composites and their application in electrochemical DNA biosensors.